2009
DOI: 10.1089/aid.2009.0080
|View full text |Cite
|
Sign up to set email alerts
|

Viral Genetic Determinants of Nonprogressive HIV Type 1 Subtype C Infection in Antiretroviral Drug-Naive Children

Abstract: Characterization of HIV-1 from slow progressors is important to facilitate vaccine and antiviral drug development. To identify virus attenuations that may contribute to slower rates of disease progression, the full-length viral genomes from primary isolates of six slow progressing HIV-positive children were sequenced. Proviral DNA was extracted from cocultured peripheral blood mononuclear cells and used to PCR amplify, sequence, and extensively analyze the near full-length genomes and LTR regions. All primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 124 publications
(141 reference statements)
3
14
0
Order By: Relevance
“…A similar reversion has been observed in a laboratory worker accidentally contaminated with a vpr-deficient strain of HIV-1 (15,16). Several studies also reported mutations in the vpr gene in long-term nonprogressor (LTNP) patients (17)(18)(19)(20). Several lines of evidence indicate that Vpr interferes with DNA repair pathways (21).…”
supporting
confidence: 60%
“…A similar reversion has been observed in a laboratory worker accidentally contaminated with a vpr-deficient strain of HIV-1 (15,16). Several studies also reported mutations in the vpr gene in long-term nonprogressor (LTNP) patients (17)(18)(19)(20). Several lines of evidence indicate that Vpr interferes with DNA repair pathways (21).…”
supporting
confidence: 60%
“…A similar reversion was observed in a laboratory worker accidentally contaminated with a vpr-deficient strain of HIV-1 (36,37). Several researchers also reported mutations in the vpr gene in patients who were long-term nonprogressors (LTNP) (38)(39)(40)(41). Many activities have been described for Vpr.…”
supporting
confidence: 57%
“…16 In a recent genetic analysis involving six children ranging in age from 7 to 10 years old, two South African children infected with subtype C virus were also found to have mutations in nef predicted to alter function. 17 We hypothesized that some HIV-infected children survived from infancy to adolescence and adulthood because they were initially infected with nef-defective HIV variants, slowing the progression of disease until the availability of potent antiretroviral therapy in the late 1990s. A related possibility was considered, that the relative immaturity of cellular immune function in early childhood would render dispensable Nef functions required for immune evasion, allowing HIV to acquire mutations that impair its function.…”
mentioning
confidence: 99%